Integrative ambidexterity - Cunha, Miguel Pina e (2019)
Purpose: Organizational ambidexterity brings together the paradoxical tensions between exploration and exploitation. Embracing such paradoxical tensions depends on both separating the poles to appreciate their distinct elements and integrating them to appreciate their synergies. This paper explores integrative ambidexterity that focuses on the synergies between exploration and exploitation and theorizes these as a single, paradoxical mode of learning. Design/methodology/approach: The authors provide conceptual commentary that aims to expand the attention within the ambidexterity literature from emphasizing separation to further accommodating integration. Findings: The authors outline that attention to separating exploration and exploitation needs to be complemented with a focus on integration, hence, the notion of integrative ambidexterity. Research limitations/implications: The authors surface three processes that advance integrative ambidexterity – novelty via memory; agility via focus; and the potential for improvisation. Together, these dynamics enable organizations to achieve an alternative approach to learning and adaptation. Practical implications: Understanding “integrative ambidexterity,” stressing the synergies between exploration and exploitation, extends the understanding of the nature and approaches to creating learning organizations. The authors three practices offer a potential blueprint to do so. Originality/value: Previous scholarship emphasized how leaders can separate exploration and exploitation by allocating these learning modes to distinct organizational units or addressing them in different time horizons. However, extant authors have less insight about the integration and synergies between exploration and exploitation, and the organizational factors that advance such integration.